Pelecehan Seksual, Kesehatan Mental,dan Kesejahteraan Sosial - Widinarsih, Dini (UI Scholars Hub, 2006)
The aim of this article is overspread the information in the subject of sexual harassment. In this article, there are explanations about the understanding of sexual harassment, the classification of variety of sexual harassment, the causes of sexual harassment, the prevention of sexual harassment, and problems of mental health psychology that is caused by sexual harassment. The expectation of this article is to improve the understanding of sexual harassment, there for it can alleviate the violence to women.